Host immune responses and vaccination against avian pathogenic Escherichia coli - RETRACTED. Issue 1 (1st March 2017) - Azeem, T.; Abid, S.A.; Ahmad, W.; Aslam, A.; Sohail, M.L.; Jaleel, S.; Umar, S.
Abstract : Avian pathogenic Escherichia coli (APEC) is one of the most economically damaging diseases affecting the poultry industry. This group of extra-intestinal E. coli causes a variety of clinical conditions including air-sacculitis and cellulitis. The economic impact of APEC is mainly due to mortality, slower growth rates and carcass downgrading. In commercial broiler operations, APEC infections are controlled indirectly by vaccination against other respiratory diseases and minimising stress conditions, and directly by administration of antimicrobial agents to suppress symptoms in infected flocks. Several studies have demonstrated that the most common virulence factors studied in APEC are rarely present in the same isolate, showing that APEC strains constitute a heterogeneous group. Different isolates may harbour different associations of virulence factors, each able to induce colibacillosis. Despite its economical relevance, the pathogenesis of colibacillosis is poorly understood. The O antigen, a component of the surface lipopolysaccharide, has been identified as a promising vaccine target. With the availability of a novel bioconjugation technology it is expected that multivalent O antigen conjugate vaccines can be produced on an industrial scale. Despite the potential for developing an efficacious vaccine to combat this economically important poultry disease, several obstacles hinder such efforts. These include cost, vaccine delivery method and timing of vaccination. The present discusses current knowledge on APEC virulence, host response to infection and various attempts to develop an effective vaccine